Nickel '96, Mineral to Market Kalgoorlie, Western Australia, 27-29 November 1996 - Grimsey, Eric; Neuss, Ian (1996)
Nickel 96 was a nickel conference held at the WA School of Mines in Kalgoorlie in 1996. It brought together 41 papers on topics ranging from exploration techniques to extraction processes, with authors from Australia, Canada, Columbia, Finland, Kazakstan, New Caledonia, Norway, China, Russia and Zimbabwe.